Reassessment of an Arabidopsis cell wall invertase inhibitor AtCIF1 reveals its role in seed germination and early seedling growth - Su, Tao; Wolf, Sebastian; Wei, Hongbin; Greiner, Steffen; Rausch, Thomas (Plant molecular biology, 2016)
In higher plants, cell wall invertase (CWI) and vacuolar invertase (VI) are recognized as essential players in sugar metabolism and sugar signaling, thereby affecting source-sink interactions, plant development and responses to environmental cues. CWI and VI expression levels are transcriptionally controlled; however, both enzymes are also subject to posttranslational control by invertase inhibitor proteins. The physiological significances of inhibitor proteins during seed germination and early seedling development are not yet fully understood. Here, we demonstrate that the inhibitor isoform AtCIF1 impacted on seed germination and early seedling growth in Arabidopsis. The primary target of AtCIF1 was shown to be localized to the apoplast after expressing an AtCIF1 YFP-fusion construct in tobacco epidermis and transgenic Arabidopsis root. The analysis of expression patterns showed that AtCWI1 was co-expressed spatiotemporally with AtCIF1 within the early germinating seeds. Seed germination was observed to be accelerated independently of exogenous abscisic acid (ABA) in the AtCIF1 loss-of-function mutant cif1-1. This effect coincided with a drastic increase of CWI activity in cif1-1 mutant seeds by 24 h after the onset of germination, both in vitro and in planta. Accordingly, quantification of sugar content showed that hexose levels were significantly boosted in germinating seeds of the cif1-1 mutant. Further investigation of AtCIF1 overexpressors in Arabidopsis revealed a markedly suppressed CWI activity as well as delayed seed germination. Thus, we conclude that the posttranslational modulation of CWI activity by AtCIF1 helps to orchestrate seed germination and early seedling growth via fine-tuning sucrose hydrolysis and, possibly, sugar signaling.